2005
DOI: 10.2134/jeq2004.0101
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal and Dissolved Phosphorus in Sandy Soils as Affected by Phosphorus Saturation

Abstract: Fertilization exceeding crop requirements causes an accumulation of phosphorus (P) in soils, which might increase concentrations of dissolved and colloidal P in drainage. We sampled soils classified as Typic Haplorthods from four fertilization experiments to test (i) whether increasing degrees of phosphorus saturation (DPS) increase concentrations of dissolved and colloidal P, and (ii) if critical DPS levels can be defined for P release from these soils. Oxalate-extractable concentrations of P, iron (Fe), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 45 publications
4
49
3
2
Order By: Relevance
“…This confirmed previous studies showing the dominance of P coll in water-extracted P in different agricultural lands (Ilg et al, 2005;Zang et al, 2013). For both studied soils, MRP coll comprised a substantial component of TP coll (RS, 59.7%; VS, 72.9%).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This confirmed previous studies showing the dominance of P coll in water-extracted P in different agricultural lands (Ilg et al, 2005;Zang et al, 2013). For both studied soils, MRP coll comprised a substantial component of TP coll (RS, 59.7%; VS, 72.9%).…”
Section: Resultssupporting
confidence: 91%
“…This fractionation neglects mobile colloids, particles ranging from 1 nm to 1 mm (Baalousha et al, 2005), by which P could be transported across long distances. Accumulated evidence indicates that colloid-facilitated P transport is an important mechanism for P transfer from agricultural land to aquatic ecosystems (Heathwaite et al, 2005;Ilg et al, 2005;Siemens et al, 2008;Regelink et al, 2013). Colloidal P (P coll ) has been reported to contribute >50% of total P (TP) in soil water samples (Hens and Merckx, 2001).…”
Section: Molecular Speciation Of Phosphorus Present In Readily Dispermentioning
confidence: 99%
See 1 more Smart Citation
“…This can have serious negative implications. Daniel et al (1998) found that concentrations of P critical for terrestrial plant growth were an order of magnitude larger than concentrations at which lake eutrophication may occur Subsurface P transport is a less studied and understood transport mechanism compared to transport by overland flow, although abundant studies have reported its occurrence [1][2][3][4][5]. For example, Andersen and Krovang (2006) modified a P Index to integrate potential P transport pathways of tile drains and leaching in Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…Surface water runoff of N and P are particularly associated with watersheds having an intense livestock or poultry presence (Akhtar et al, 2005), where the soils have been heavily fertilized (Moore and Edwards, 2005;Davis et al, 2000) or are in proximity to surface waters (Elliott et al, 2006;Gburek et al, 2000;Langlois and Mehuys, 2003;Page et al, 2005). Nitrate concentrations from subsurface drainages frequently exceed the USEPA maximum contamination levels (Abrahamson et al, 2006;Davis et al, 2000;Randall et al, 2003; and P concentrations may also be a concern, especially where the soils have a low P sorption capacity and elevated P concentrations (Djodjic et al, 2004;Ilg et al, 2005;Page et al, 2005;Anderson and Magdoff, 2005;Langlois and Mehuys, 2003;Stampfli and Madramootoo, 2006). Thus, soil classification and characterization, cropping systems and irrigation/drainage systems interact to produce various pathways for N and P to impact surface water.…”
Section: Introductionmentioning
confidence: 99%